Biomass and nutrients in an agroforestry system in the most southerly Brazil - Calil, Francine Neves; Viera, Márcio; Schumacher, Mauro Valdir; Lopes, Vicente Guilherme; Witschoreck, Rudi (Revista Ecologia e Nutrição Florestal - ENFLO, 2014)
Historically, in southerly Brazil, composed of large rural estates, meat and grains are produced in a monocultural system. In this scenario, agroforestry systems arise as an alternative to diversify rural production, also allowing the use of natural resources more efficiently. Thus, in this study, we aimed to quantify the biomass and nutrients contained in the different components of an agroforestry system (eucalyptus + sorghum/sunflower/canola) in the extreme south of Brazil. The eucalyptus was planted at spacing 10.0 m x (3.0 m x 2.0 m) and agricultural crops were sown manually between rows of the forest species, during the initial three years. We determined the biomass and nutrient content of sorghum (leaves, grain and stem), sunflower (leaves, stem, grains and flowers), canola (grain, stem and pod) and eucalyptus (leaves, branches, bark and wood) at 18 months of age. The biomass of sorghum was 9,866.3 kg ha-1 (17.6% leaves, 47.8% stem and 34.6% grain); of sunflower 11,958.1 kg ha-1 (21.6% grains and flowers, 24.0% leaves, 21.3% grain and 33.0% stem), of canola 4,651 kg ha-1 (46.1% stem, 28.2% seeds and 25.7% pod) and eucalyptus 10,974.3 kg ha-1 (45.3% wood, 8.4% bark, 26.3% branches and 20.0% leaves). The productivity of the agricultural components of an agroforestry system was considered satisfactory, and the harvesting is recommended only for the main grain fraction, responsible for P export